2014
DOI: 10.1111/spc3.12090
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Consistency Processes in Social Cognition: Explicit‐Implicit Discrepancies Across Systems of Evaluation

Abstract: What happens when our automatic evaluations conflict with our attitudes that we can reflect on and articulate? In this paper, we review some processes by which explicit implicit evaluative discrepancies (EIEDs) arise and can impact our thoughts, feelings, and behavior, using a dual-systems perspective on attitudes to explain the psychological processes underlying these evaluative inconsistencies. EIEDs emerge when differential positive and negative evaluations toward attitude objects reside in systems of knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…This is an interesting finding considering that students reported that they would consider university SET more seriously than RMP evaluations. This incongruity between students' explicit attitude and implicit response toward university SET aligns with social psychological findings indicating that individuals frequently possess inconsistent attitudes (Shoda et al, 2014). Although explicit attitudes may be easier to verbalize (e.g., "I would consider university SET more seriously"), inconsistent implicit attitudes still exert a strong influence on behavior (e.g., consider university SET and RMP evaluations equally seriously) (Karpen et al, 2012).…”
Section: Course Decision-makingsupporting
confidence: 72%
“…This is an interesting finding considering that students reported that they would consider university SET more seriously than RMP evaluations. This incongruity between students' explicit attitude and implicit response toward university SET aligns with social psychological findings indicating that individuals frequently possess inconsistent attitudes (Shoda et al, 2014). Although explicit attitudes may be easier to verbalize (e.g., "I would consider university SET more seriously"), inconsistent implicit attitudes still exert a strong influence on behavior (e.g., consider university SET and RMP evaluations equally seriously) (Karpen et al, 2012).…”
Section: Course Decision-makingsupporting
confidence: 72%
“…31 Researchers have argued that EIEDs can hinder self-regulatory mechanisms for behaviour. 32,33 Therefore, achieving goal-directed movements such as the translation of intentions into action may be affected by discrepancies between explicit and implicit motives for exercise engagement. 34 The majority of research on implicit processes related to exercise intentions has been done within already exercising populations.…”
Section: The Intention Behaviour Gap In Exercisementioning
confidence: 99%
“…Researchers have also argued that discrepant explicit and implicit evaluations result in less behaviour when self-regulatory mechanisms are low 32,33 . Research in dietary behaviours has found that the influence of explicit processes on dietary behaviour are reduced when selfregulation is depleted, whereas the effects of implicit processes are increased 42 .…”
Section: The Intention Behaviour Gap In Exercise 15mentioning
confidence: 99%
See 1 more Smart Citation
“…What kind of relationship-in the case of domestic violence-is this coparenting or trying to salvage a marriage? At the within-person level, we seem to have a capacity and tolerance for internal inconsistency of which we are not aware (Shoda, McConnell, & Rydell, 2014), but less tolerance for internal inconsistency of which we are aware (Festinger, 1957). So, the more we are aware of competing narratives within ourselves, the greater the press to organize those competing narratives.…”
Section: Narrative Research As Interventionmentioning
confidence: 99%